Free‐breathing, non‐ECG, continuous myocardial T1 mapping with cardiovascular magnetic resonance multitasking. Issue 4 (19th November 2018) - Shaw, Jaime L.; Yang, Qi; Zhou, Zhengwei; Deng, Zixin; Nguyen, Christopher; Li, Debiao; Christodoulou, Anthony G.
Abstract : Purpose: To evaluate the accuracy and repeatability of a free‐breathing, non‐electrocardiogram (ECG), continuous myocardial T1 and extracellular volume (ECV) mapping technique adapted from the Multitasking framework. Methods: The Multitasking framework is adapted to quantify both myocardial native T1 and ECV with a free‐breathing, non‐ECG, continuous acquisition T1 mapping method. We acquire interleaved high–spatial resolution image data and high–temporal resolution auxiliary data following inversion‐recovery pulses at set intervals and perform low‐rank tensor imaging to reconstruct images at 344 inversion times, 20 cardiac phases, and 6 respiratory phases. The accuracy and repeatability of Multitasking T1 mapping in generating native T1 and ECV maps are compared with conventional techniques in a phantom, a simulation, 12 healthy subjects, and 10 acute myocardial infarction patients. Results: In phantoms, Multitasking T1 mapping correlated strongly with the gold‐standard spin‐echo inversion recovery (R 2 = 0.99). A simulation study demonstrated that Multitasking T1 mapping has similar myocardial sharpness to the fully sampled ground truth. In vivo native T1 and ECV values from Multitasking T1 mapping agree well with conventional MOLLI values and show good repeatability for native T1 and ECV mapping for 60 seconds, 30 seconds, or 15 seconds of data. Multitasking native T1 and ECV in myocardial infarction patients correlate positively with values from MOLLI. Conclusion: Multitasking T1 mapping can quantify native T1 and ECV in the myocardium with free‐breathing, non‐ECG, continuous scans with good image quality and good repeatability in vivo in healthy subjects, and correlation with MOLLI T1 and ECV in acute myocardial infarction patients.